Wizja Polski w świadomości chłopów - Brodowska-Kubicz, Helena (Acta Universitatis Lodziensis. Folia Historica, 1980)
The vision of Poland in the minds of peasants was overshadowed by memories of soccage, exploitation of nobility, and power yielded by lords. They also had vivid memories, especially those living in the Russian sector of partitioned Poland, of the Kosciuszko insurrection –1794 and, even more so, of the January insurrection in 1863. Favouring more and more strongly the concept of free Poland along with development of their social and national awareness, the peasants voiced in favour of the republican and democratic Poland. Some others wanted a monarchy with a constitution and parliament in Warsaw elected by the whole nation directly in secret vote on principles of equality. Programmes of peasants' parties established in the Austrian sector towards the end of 19th century and in the Russian sector at the beginning of 20 the century were giving support to reunion of Polish territories divided into three sectors, and establishment of the Polish state in its ethnic boundaries. The supreme state authority was to be represented either by the nominated king or the president elected every few years. All peasants' parties aimed at abolishment of big landed properties along different principles and establishment of a new agrarian structure composed of small, independent farms. There was postulated development of education, foundation of agricultural schools, common and free primary schools, and generally accessible secondary and higher schools. There were put forward proposals concerning equal civil rights for women, and equal pay for working women and men. There was voiced a principle of religious tolerance for all religions and that of granting equal rights to ethnic minorities. The new Poland was to possess close friendship ties with Lithuania and Russia. There were also projects of establishing a federation of European states, and a utopian vision of Poland – as a big co-operativo unit. Co-operative forms of organization, of production, trade, and supply verified in practice found their permanent place in the economic model of the People's Poland. Thus the peasants supporting the struggle for independence of the country and characterized with a high degree of awareness wished to have a country with social justice and equality, a future mother-country for all its citizens. With such convictions they were joining the independence movement organized shortly before the outbreak of the 1st World War and during its course. This independence movement, in turn, was providing a stimulus for other politically unaware peasants, who were self-sacrificingly supporting the movement setting up the Polish Military Organization. Regaining of the national independence in 1918 was welcomed with joy by peasants, with the desire of working for their mother-country and reconstructing it; they would ask their sons to join the Polish army hoping that they would be better off in the new and independent Poland than in the country partitioned by foreign powers. They were also expressed once in a while critical opinions to the effect that the new Poland should not become a country of lords. The author has based her article on programmes of peasants' parties, press correspondence and memoirs of peasants.